Effect of HfN, HfC and HfB2 additives on phase transformation, microstructure and mechanical properties of ZrO2-based ceramics. Issue 5 (1st April 2018) - Song, Jinpeng; Cao, Lei; Jiang, Longkai; Liang, Guoxing; Gao, Jiaojiao; Li, Dongxu; Wang, Shiying; Lv, Ming
Abstract: ZrO2 -based ceramics were fabricated by the hot pressing sintering technology at 1550 ℃. Effect of HfN, HfC and HfB2 additives on their phase transformation, microstructure and mechanical properties were investigated. The m-ZrO2 was not discovered in ZrO2 -HfC ceramics but discovered in ZrO2 -HfN and ZrO2 -HfB2 ceramics, which indicated that HfC potentiated the effect of Y2 O3 stabilizer on inhibiting phase transformation and that to some extend HfN and HfB2 undermined this effect. Meanwhile, HfC can inhibit the ZrO2 grain growth or amalgamation to form fine ZrO2 grains in ZrO2 -HfC ceramics, whereas HfN and HfB2 probably induced the ZrO2 grain growth or amalgamation to form big ZrO2 grains in their ceramics. And the bonding strength between HfB2 and ZrO2 higher than the other two was approximately inferred from the observed grain boundary-interface dihedral angles between the ZrO2 grain and these particles (HfC, HfN and HfB2 ). Fracture model of these ceramics was the mixed inter/transgranular fracture model. When the additive content – HfN, HfC and HfB2 content - increased from 5 wt% to 15 wt%, the pinning effect of HfN particle in ZrO2 -HfN ceramics as well as fine ZrO2 grains in ZrO2 -HfC ceramics and the high bonding strength between the ZrO2 grain and HfB2 particle in ZrO2 -HfB2 ceramics played a dominant role in improving the flexural strength and fracture toughness; meanwhile, the improved Vickers hardness of these ceramics was mainly attributed to the increase of hard additive content. However, when these additives content increased to 20 wt%, many big micro-voids in ZrO2 -HfN and ZrO2 -HfC ceramics and big ZrO2 grains in ZrO2 -HfB2 ceramic produced negative effect on mechanical properties. In these ceramics, ZrO2 -15 wt%HfB2 ceramic showed the optimum mechanical properties: flexural strength of 1093.06 ± 24 MPa, fracture toughness of 8.17 ± 0.18 MPa m 1/2 and Vickers hardness of 14.37 ± 0.21 GPa.